A SHORT CRITIQUE OF MINIMUM SENTENCES - Alphonso Goliath (Obiter, 2023)
The state has a constitutional duty to respect, promote and protect the rights of citizens. To this end, every citizen has the right to dignity, the right to equality, and the right to freedom and security of the person. Allied thereto is that they will not be subjected to punishment that is cruel, inhuman, and degrading, among others. With the advent of democracy, South Africa inherited a host of challenges and one of these challenges was the explosion of violent crime. Mandatory minimum sentences were introduced by the Criminal Law Amendment Act 105 of 1997 to serve as a temporary, emergency crime-control measure based on the commonly-held belief that harsh punishment would reduce crime. Since minimum sentencing legislation has been in full operation for more than two decades, one would expect crime in South Africa to be relatively under control. However, violent crimes like murder and rape in our society have not abated. It is argued that minimum sentences do not serve as a deterrent to violent crime, instead, they exacerbate prison overcrowding. Lengthy prison terms and high imprisonment rates fuel the conditions for higher crime rates as it impedes the objectives of rehabilitation and promotes recidivism. The state’s continued support for these increased sentences infringes on the constitutional rights of citizens. In this article, the author concludes that if we feel outraged by the high rate of violent crime, we need to find a sentencing regime that leads to the reduction rather than the exacerbation of crime in line with constitutional provisions.